Perception and attitudes of heterosexual males on homosexual males as friend - Misa, Maria Clara E.; Quizon, Irene Aprilis M.; Savella, Mariel Joy O. (2009.)
Freindship between homosexual males are rarely studied. This is why this study is focused on the perceptions and attitudes of heterosexual male young adults toward homosexual male as friends. The data gathering procedures consisted of collecting survey questionnaires which were accomplished by 100 heterosexual males aged 19 to 22 years studying in the University of the Philippines in Diliman followed by two focus group discussions for a deeper analysis. The results showed that 50% were neutral in liking homosexual males a friends, 35% like homosexual males as friends and the remaining 15% do not like homosexual males as friends. The first group was called the Agree Group consisting of five participants who agreed to the statement "I like homosexual males as friends" while the second group was called the Disagree Group and consisted of four participants who disagreed the said statement. High-spiritedness and sociability are examples of likeable traits of homosexual males as friends while being boisterous and flirtatious are examples of least likeable ones. The positive perceptions turned out to be the most likeable traits of homosexual males a friends while the negative perceptions turned out to be the least likeable traits of homosexual males as friends while the negative perceptions turned out to be the least likeable traits of homosexual males as friends. Heterosexual males also utilize their criteria on most likeable and least likeable traits that they consider in homosexual males as friends as standards in deciding whether to have or not to have homosexual males as friends. Factors and reasons influencing these perceptions and attitudes turned out to be personal encounters with homosexual males, impact of societal norms, religion, family opinions and teachings, and the media. The researchers recommend future studies to be conducted to a larger sample and to explore other aspects of homosexuality.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Friendship; Gay men -- Relations with heterosexuals -- Philippines